Mise en scène and film style from classical Hollywood to new media art - Martin, Adrian 1959- (Palgrave close readings in film and television, 2014)
"Styles of filmmaking have changed greatly from the classical Hollywood system, with its emphasis on narrative and character, to the current digital era of YouTube and installation art, where audiovisual spectacle takes command. The ways in which film critics and scholars have analysed these transformations in film style have also often changed. This book explores two central style concepts from the history of audiovisual criticism and theory, mise en scène and dispositif, to illuminate a wide range of film and new media examples. It argues that we need an open, inclusive and truly international approach to understand anew both old and current film and media works"..